(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
One hundred patients of allergic rhinitis were diagnosed and treated during the period of January 2006 to December 2006. The patients belonged to different age group. Among them patients from 20-29 year of age group are commonly affected (43%). Female (33%) are more sufferer than male. In our study most of the patients are student (38%). House dusts mites (73%), and cold (48%), are the common etiological factors. Majority of the patients presented with sneezing (91%). we got 19% patients with co-morbid allergic conjunctivitis and sinusitis. Patients were treated with more than one drug, mainly with oral antihistamine (91%), nasal steroid (32%) and other medications. In this study, we concluded that oral antihistamine and nasal corticosteroids are the good options to treat allergic rhinitis. Key Words: Allergic rhinitis; Seasonal; Perennial. DOI: 10.3329/bjo.v16i1.5780 Bangladesh J Otorhinolaryngol 2010; 16(1): 44-47